KONTRIBUSI KONSEP DIRI DAN PEMANFAATAN FASILITAS PRAKTIKUM TERHADAP HASIL BELAJAR DASAR LISTRIK ELEKTRONIKA - Nanda Saputra; Nelda Azhar (Universitas Negeri Padang, 2019)
This study aims to determine the Contribution of Self Concept and Utilization of Practical Facilities to the Learning Outcomes of Basic Electricity Electronics in Class X Students of Audio Video Engineering at SMK Negeri 5 Padang. The population of this study was 93 students. This type of research is descriptive correlational. In this study using (Simple Random Sampling) with a total of 50 students. Data on student learning outcomes were obtained from Basic Electrical Electronics subject teachers at SMK Negeri 5 Padang. While the self-concept data and utilization of practicum facilities were collected through questionnaires using a Likert scale that has been tested for validity and reliability. The results of data analysis showed: (1) Self-concept and utilization of practicum facilities together contributed a contribution of 47.88% to student learning outcomes; (2) Self concept contributes 21.34% to student learning outcomes; (3) Utilization of practicum facilities contributed 31.47% to learning outcomes. So it can be concluded that the self concept and utilization of practicum facilities contribute to the learning outcomes at SMK Negeri 5 Padang.Keywords: Self-Concept, Utilization of Practical Facilities, Learning Outcomes.